2017
DOI: 10.1177/0266666917735879
|View full text |Cite
|
Sign up to set email alerts
|

The possible benefits of freedom of information laws to the records management landscape in the ESARBICA region

Abstract: This paper seeks to demonstrate how records and archives management in the Eastern and Southern African Branch of the International Council on Archives (ESARBICA) can benefit from the enactment of freedom of information legislation if backed by political will, trained records and information management personnel and infrastructure. Examples of how properly crafted FOI legislation have or have not benefited records and archives management in other countries have been presented. The findings of this study show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The review of the literature shows that most of the countries experience a challenge of weak legislation to promote accountability and transparency (Okello-Obura, 2011). This statement is supported by Khumalo and Baloyi (2017) who found that most of the national archive institutions are not yet updated and are inadequate to address concerns relating to digital records.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The review of the literature shows that most of the countries experience a challenge of weak legislation to promote accountability and transparency (Okello-Obura, 2011). This statement is supported by Khumalo and Baloyi (2017) who found that most of the national archive institutions are not yet updated and are inadequate to address concerns relating to digital records.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Namibia is in the process of enacting a freedom of information law, with its Draft Access to Information Bill of April 2017. Authors such as Khumalo and Baloyi (2017) and Mnjama (2003) agree that without adequate records and information management systems which require trained and skilled personnel, a freedom of information law is not effective. “Access to information hinges on the presence of adequate records and information management systems, which guarantee the management of records throughout their life cycle” (Khumalo and Baloyi, 2017, p. 3).…”
Section: Records Management Challenges In Namibiamentioning
confidence: 99%
“…The public sector in South Africa is characterised by ineffective record-keeping, which ultimately has a detrimental impact on the protection of various fundamental human rights such as the right of access to information. Several scholars such as Mojapelo (2017), Mojapelo and Ngoepe (2017), Khumalo and Baloyi (2019) emphasised the close connection between public sector record-keeping and the right of access to information. For example, Mojapelo and Ngoepe (2017) point out that effective systems of record-keeping are important for the right of access to information to be realised.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mojapelo and Ngoepe (2017) point out that effective systems of record-keeping are important for the right of access to information to be realised. Furthermore, in a study conducted by Khumalo and Baloyi (2019) to examine how records and archives in Eastern and Southern African Branch of the International Council on Archives (ESARBICA) would benefit from the implementation of freedom of information legislation, it was found that freedom of information could benefit records and archives in the region by encouraging the development of proper record-keeping systems, formalisation and standardisation of records management practice and continuous training of records practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation